(untitled) (Research, Society and Development, 2022)
This work experimentally presented the effect of soil compaction, the footing size (l) and overload on the pull-out capacity of L-shaped anchor laid in sandy clayey soil from load displacements curves obtained in tests of static pull-out. The inclined load, arising from the configuration of guyed towers, develops horizontal and vertical response of the anchor and most of the articles until now focused on the study of anchor seated in a horizontal or vertical position, in addition to not verifying the influence of length/width and its three-dimensional effect. Thirteen experimental pullout tests were performed with progressive weight increases until the soil rupture, noting the respective displacements in L-shaped anchor with four different lengths: 20 cm, 15 cm, 10 cm and 5 cm. Analyzing tension versus footing size (l) behaviour, it was verified that load capacity does not present a constant linear increasing variation. For anchors with short length, the mobilized tension increases considerably as the contact area decreases, probably developing a puncture failure in soil. From the length equal to 10 cm, the behaviour begins to follow the assumption by Terzaghi (1943) with linear growth of pull-out capacity. This work finally presents a theoretical values of shape factors Nc, Nq and Nγ , influenced by the applied load and the soil compaction.